(untitled) (SCIENCE TIME JOURNAL, 2026)
. The selection and development of teaching materials for learners of different age groups remains one of the key issues in foreign language teaching methodology. Effective instructional materials should correspond to learners’ cognitive, psychological, linguistic, and social characteristics. This article examines the methodological principles of designing and adapting foreign language learning materials for children, adolescents, and adult learners. Particular attention is given to age-related differences in motivation, learning styles, language needs, and communicative abilities. The study highlights the importance of creating age-appropriate materials that promote learner engagement, language acquisition, and communicative competence. The findings suggest that well-designed materials significantly contribute to the effectiveness of the teaching and learning process across different educational contexts.